(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2022)
This literature review article analyzes research carried out on educational policy in Brazil. The educational policy discipline plays a fundamental role in the training of pedagogues and teachers, aiming at their instrumentalization for analysis and action in relation to educational policies. By reviewing the existing literature, this article sought to identify key research trends, gaps in knowledge, and the contributions of studies conducted to date. The main focus of research has been on the curricular aspects of the discipline and the analysis of the teaching process based on teaching activities. It is necessary to broaden the discussions by providing analyzes on theoretical aspects, theoretical-methodological models for teaching educational policy, and the students’ perception of training in the context of the discipline. Keywords: Discipline Educational Policy. Educational politics. Literature review.